Using Podcasts as Listening Formative Assessment Materials in EFL Flipped Classroom Instruction - Hibatulloh, Muhammad Firnas; Aini, Nurul (Proceeding International Conference on Religion, Science and Education, 2024)
Flipped classroom interaction is getting popular to be chosen by the teachers to deliver the language teaching and its assessment, including listening. Podcasts as one of the media, can be an authentic material used. It is because podcasts are interesting and attract students’ attention which can lead to improvement in their learning activity. This article aims to introduce podcasts as listening formative assessment materials in flipped classroom instruction for EFL students. It integrates the podcasts along the prior, during, and after instruction of listening formative assessment which will be deliberate more in the face-to-face class section. The combination itself concerns the technology media and communicative learning in class which is actually how flipped class instruction is running.